Water treatment filter element and preparation method thereof
By adopting a double-layer filter element structure and combining the porous structure of activated carbon and ceramic powder, the compressed activated carbon filter element has solved the problem of large water resistance and slow water effluent speed, achieving more efficient water quality purification and improving water effluent speed.
Patent Information
- Application Number
- CN202411647955.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-07
AI Technical Summary
The compressed activated carbon filter element has the problems of large water resistance pressure and slow water effluent speed, and the preparation process of the prior art ceramic-based porous sewage treatment agent is complicated.
A double-layer filter element structure is adopted, wherein the inner layer is activated carbon material and microbead material with open pores, and the outer layer is ceramic powder with pores distributed from nano-scale to micro-scale and microbead material with open pores. The water resistance is reduced through physical and chemical adsorption and the water outlet pressure is increased.
It effectively reduces the adsorption burden of activated carbon, reduces the water resistance pressure, increases the water outlet speed of the water purifier, and maintains an efficient water purification effect.
Smart Images

Figure CN119565228A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water purification, and in particular relates to a water treatment filter element and a preparation method thereof. Background Art
[0002] Activated carbon is a multi-aperture carbonized product with rich pore structure, so it has good adsorption characteristics. High-quality activated carbon also has the characteristics of high surface area. The specific surface area of each gram of activated carbon can be equivalent to as much as 1,500 square meters. Taking advantage of the porosity and large specific surface area of activated carbon, it can effectively adsorb organic matter, discoloration, odor and other substances in water, thereby achieving the purpose of purifying water quality. Activated carbon is usually used for terminal filtration of water purifiers to improve the taste of drinking water.
[0003] According to the structural characteristics of the activated carbon filter element, it can be divided into compressed activated carbon filter element and bulk activated carbon filter element: the compressed activated carbon filter element uses activated carbon with high adsorption value as the filter material, and is compressed and sintered with food-grade adhesive. The inside and outside of the compressed activated carbon filter element are wrapped with a layer of non-woven fabric with filtering function to ensure that the carbon core itself will not drop carbon powder. Soft nitrile rubber sealing pads are installed at both ends of the carbon core to ensure that the carbon core has good sealing when installed in the filter cartridge. The compressed activated carbon filter element has a high density, the activated carbon particles are uniform in size, the filtering effect is stable, and it can reduce particulate pollution, but the resistance is large, the water output is slow, and the service life is relatively short.
[0004] The bulk activated carbon filter element is to load the required activated carbon particles into a special plastic shell, weld the end caps to the two end faces of the shell with welding equipment, and put non-woven filter sheets for filtering at both ends of the shell to ensure that the carbon core will not drop carbon powder and black water when in use. Bulk activated carbon filter elements are suitable for different filter containers and have a relatively long service life, but the filtering effect is relatively inferior to that of compressed activated carbon filter elements.
[0005] Chinese patent application 201910268521.8 discloses a pure water taste regulator, in which Ru porcelain, microcrystalline activated carbon, and polypropylene polymer materials are mixed and stirred evenly, and then the mixture is loaded into a cylindrical mold and compacted, sintered in a high-temperature (370-380°C) furnace for 4 hours, and then annealed to obtain a cylindrical filter element, which is loaded into a filter shell of matching size to obtain a pure water taste regulator, which has the effect of reducing water molecule clusters. However, the material does not have a micro-nano pore structure, has large water resistance during use, and has a short service life.
[0006] Chinese patent application 202310564564.7 discloses a ceramic-based porous sewage treatment agent and a preparation method thereof. The porous ceramic is modified by polyethyleneimine, and the hydroxyl groups on the surface of the ceramic material are modified into amino groups. Then, in an alkaline environment, the amino groups react with carbon disulfide to introduce a dithioamino structure with a stronger adsorption effect on heavy metal ions, further improving the adsorption capacity of porous ceramics for heavy metal ions. The provided ceramic-based porous sewage treatment agent has good reproducibility. After 10 cycles of adsorption-analysis, the adsorption capacity for heavy metals can still reach more than 80% of the initial capacity. However, the modification process of this patent is relatively complicated.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The purpose of the present invention is to provide a water treatment filter element and a preparation method thereof, which aims to improve the water quality and the water outlet speed of a water purifier while addressing the problems of high water resistance pressure and slow water outlet speed of a compressed activated carbon filter element.
[0009] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0010] The present invention provides a water treatment filter element, comprising a double-layer filter element structure of an inner layer and an outer layer; one of the inner layer and the outer layer comprises an activated carbon material and a microbead material with open pores, and the other layer comprises a ceramic powder with pores distributed from nanometer to micrometer level and a microbead material with open pores.
[0011] If the inner layer includes the ceramic powder and the second microbead material with open pores, the outer layer includes the activated carbon material and the first microbead material with open pores; it can also be the opposite, the inner layer includes the activated carbon material and the first microbead material with open pores, and the outer layer includes the ceramic powder and the second microbead material with open pores.
[0012] Preferably, the activated carbon material is compressed activated carbon, and the specific surface area of the activated carbon material is 500-1500m 2 / g.
[0013] The water treatment filter element of this structure can reduce the adsorption burden of activated carbon by physically and / or chemically adsorbing heavy metal ions, organic matter, discolored and odorous substances in water. By reducing the thickness of compressed activated carbon, the water resistance generated by filtration is reduced and the water outlet pressure is increased.
[0014] The water treatment filter element is made of pure natural inorganic materials, so no secondary pollution will be generated during the use of the water purifier. Unlike pure water machines, it does not remove all kinds of minerals in the water, but retains the beneficial minerals in the water, while effectively removing mud, sand, bacteria, rust, etc. It has the advantages of no clogging, long service life, excellent filtering effect, and sweet purified water. At the same time, it can adapt to very bad water conditions.
[0015] The present invention also provides a method for preparing the water treatment filter element, comprising uniformly mixing the microbead material 1 and the activated carbon powder and then pressing them to obtain the core material 1;
[0016] The micro-bead material 2, ceramic powder and binder are mixed evenly, molded, sintered, and then assembled with the core material to form an inner and outer layer to obtain the product.
[0017] In the core material one, the microbead material one is mixed with activated carbon to facilitate the compaction of the activated carbon. At the same time, it acts as a hydrophilic medium in the activated carbon to guide the water flow to pass evenly, improve the contact of the activated carbon, and allow the activated carbon to play an adsorption and filtration role. It is mainly to improve fluidity, and secondly its own adsorption performance. Therefore, the microbead material one with relatively large stacking density, low porosity and relatively high strength is selected.
[0018] The outer layer of micro-bead material mixed with ceramic powder is relatively light and has a high porosity, and its micro-nano pore size is utilized to improve the filtering performance.
[0019] Furthermore, the microbead material 1 and activated carbon powder are 20-40 parts and 60-80 parts by mass respectively.
[0020] Preferably, the particle size of the activated carbon is 1-150 μm.
[0021] Preferably, the particle size of the microbead material 1 is 100-300 μm, and the bulk density is 0.75-0.85 g / cm 3 , porosity 30-40%.
[0022] The combination of the particle sizes of the microbead material and the activated carbon powder is beneficial to the molding process by the pressing process on the one hand, and can also improve the density of the activated carbon rod on the other hand.
[0023] Furthermore, the microbead material 2, ceramic powder and binder are 40-60 parts, 90-110 parts and 0.1-5 parts by mass respectively.
[0024] Preferably, the particle size of the microbead material 2 is 0-250 μm, and the bulk density is 0.40-0.50 g / cm 3 , porosity 75-85%, pore size range 5nm-1μm, specific surface area 180-195m 2 / g.
[0025] Furthermore, the molding is performed by maintaining the pressure at 5-30 MPa for 40-80 seconds and then demolding and removing.
[0026] Furthermore, the sintering is to sinter the formed product at 800-1000° C. for 60-120 min.
[0027] Preferably, the method for preparing the ceramic powder comprises: dissolving the ceramic powder raw material in an organic solvent, adding polyurethane and a surface modifier thereto for reaction, titrating to form, and then sintering to obtain the ceramic powder.
[0028] Optionally, the organic solvent includes one or more of dimethylformamide, tetrahydrofuran, dichloromethane or dimethyl sulfoxide.
[0029] Optionally, the surface modifier includes one or more of oxalic acid, malonic acid, succinic acid, glutaric acid or adipic acid.
[0030] Preferably, the ceramic powder raw material includes one or more of kaolin, purple clay or red clay.
[0031] Preferably, the specific surface area of the ceramic powder is 10-300m 2 / g, particle size is 20-300μm.
[0032] Preferably, the preparation method of the micro-bead material 1 and the micro-bead material 2 is a conventional process, including: preparing the diatomaceous earth raw material into a slurry, grinding it, adding different amounts of foaming agent, spray drying and forming it, and then sintering the green body at 800-900°C to obtain it.
[0033] More preferably, the foaming agent comprises CTAB in an amount of 0-1% by mass of the slurry.
[0034] Optionally, the binder is a solution of sodium carboxymethyl cellulose and / or polyvinyl alcohol; further, the concentration of the solution is 0.2-5%.
[0035] The present invention changes the homogeneous single filter element structure into a double-layer composite structure, one of which is made of micro-bead material with high porosity. The second layer is formed by molding and sintering ceramic powder with micro-nano pore structure and binder. The pore size of this structure has a large span, from micron to nanometer, and can physically and chemically adsorb heavy metal ions, organic matter, heterochromatic and odorous substances in water before the compressed activated carbon filter element. The rich pore structure can achieve more lasting adsorption, reduce the adsorption burden of activated carbon, reduce the water resistance pressure of compressed activated carbon, and increase the water outlet speed of the water purifier. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 This is a schematic diagram of the cross-sectional structure of the water treatment filter element obtained in Example 1 of the present invention;
[0038] Figure 2 This is the appearance and cross-sectional structure diagram of the water treatment filter element obtained in Example 1 of the present invention.
[0039] Explanation of the reference numerals: 1- compressed activated carbon filter layer; 2- ceramic powder molding layer. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] A water treatment filter element, such as Figure 1 and Figure 2 As shown, a double-layer filter element structure including an inner layer and an outer layer; the inner layer is a compressed activated carbon filter layer 1, including activated carbon material and a micro-bead material with open pores; the outer layer is a ceramic powder molding layer 2, including ceramic powder with pore distribution from nanometer to micrometer level and a micro-bead material with open pores.
[0043] The particle size of the activated carbon powder is 1-150 μm, and the specific surface area is 1200 m 2 / g.
[0044] The particle size of the microbead material 1 is 100-300 μm, and the bulk density is 0.8 g / cm 3 , porosity 35%.
[0045] The particle size of the microbead material 2 is 0-250 μm, and the bulk density is 0.45 g / cm 3 , porosity 80%, pore size range 5nm-1μm, specific surface area 188m 2 / g.
[0046] The specific surface area of the ceramic powder is 153 m 2 / g, particle size is 20-300μm.
[0047] The preparation method is as follows:
[0048] S1: According to the method of Example 1 disclosed in Chinese patent application CN111484351A, the alumina ceramic powder is replaced with kaolin. That is:
[0049] S1a: 100 g of kaolin with a particle size of 5 μm was added to 435 g of dimethylformamide solvent and mixed and ball-milled for 12 h to prepare a uniformly dispersed ceramic slurry;
[0050] S1b: Add 25 g of hydroxyl-terminated thermoplastic polyurethane and 20 g of oxalic acid, a surface modifier, to the obtained ceramic slurry, and stir the mixture at 80°C for 4 h to obtain a casting solution with a solid content of 25 wt%, wherein the mass ratio of the surface modifier to kaolin is 0.2, and the mass ratio of the polyurethane to kaolin is 0.25;
[0051] S1c: The obtained casting liquid is filled into a syringe, and deionized water is added drop by drop to solidify in a coagulation bath. After standing for 12 hours, it is dried at 45°C for 24 hours to obtain a ceramic powder body; the body is debinded at 600°C for 2 hours, and sintered at 1550°C for 3 hours to obtain the ceramic powder.
[0052] S2: 40g of micro-bead material 1 and 60g of activated carbon powder were pressed into core material 1, 50g of micro-bead material 2, 100g of ceramic powder and 2g The binder (sodium carboxymethyl cellulose with a concentration of 4%) is mixed evenly; placed in a mold and maintained at a pressure of 20 MPa for 60 seconds, then demolded and taken out; sintered at 950°C for 90 minutes, and then the obtained core material 1 (compressed activated carbon filter layer 1) is sleeved in a circular ceramic layer body (ceramic powder molding layer 2) to synthesize the inner and outer layers.
[0053] Example 2
[0054] A water treatment filter element, comprising a double-layer filter element structure of an inner layer and an outer layer; the inner layer is a compressed activated carbon filter layer 1, comprising an activated carbon material and a microbead material with open pores; the outer layer is a ceramic powder molding layer 2, comprising a ceramic powder with pore distribution from nanometer to micrometer level and a microbead material with open pores.
[0055] The specific surface area of the ceramic powder is 78m 2 / g, particle size is 20-300μm.
[0056] The particle size of the activated carbon powder is 1-150 μm, and the specific surface area is 1200 m 2 / g.
[0057] The particle size of the microbead material 1 is 100-300 μm, and the bulk density is 0.75 g / cm 3 , porosity 30%.
[0058] The particle size of the microbead material 2 is 0-250 μm, and the bulk density is 0.40 g / cm 3 , porosity 75%, pore size range 5nm-1μm, specific surface area 183m 2 / g.
[0059] The preparation method is as follows:
[0060] The preparation method of ceramic powder is the same as that in Example 1.
[0061] 30g of micro-bead material 1 and 80g of activated carbon powder were pressed into core material 1, and 60g of micro-bead material 2, 110g of ceramic powder and 2g The binder (sodium carboxymethyl cellulose with a concentration of 5%) is mixed evenly; placed in a mold and maintained at a pressure of 15 MPa for 70 seconds, then demolded and taken out; sintered at 850°C for 80 minutes, and then the obtained core material 1 (compressed activated carbon filter layer 1) is sleeved in a circular ceramic layer body (ceramic powder molding layer 2) to synthesize the inner and outer layers.
[0062] Example 3
[0063] A water treatment filter element, comprising a double-layer filter element structure of an inner layer and an outer layer; the inner layer is a compressed activated carbon filter layer 1, comprising an activated carbon material and a microbead material with open pores; the outer layer is a ceramic powder molding layer 2, comprising a ceramic powder with pore distribution from nanometer to micrometer level and a microbead material with open pores.
[0064] The specific surface area of the ceramic powder is 78m 2 / g, particle size is 20-300μm.
[0065] The particle size of the activated carbon powder is 1-150 μm, and the specific surface area is 1200 m 2 / g.
[0066] The particle size of the microbead material 1 is 100-300 μm, and the bulk density is 0.85 g / cm 3 , porosity 40%.
[0067] The particle size of the microbead material 2 is 0-250 μm, and the bulk density is 0.50 g / cm 3 , porosity 85%, pore size range 5nm-1μm, specific surface area 190m 2 / g.
[0068] The preparation method is as follows:
[0069] The preparation method of ceramic powder is the same as that in Example 1.
[0070] 20g of micro-bead material 1 and 70g of activated carbon powder were pressed into core material 1, and 40g of micro-bead material 2, 90g of ceramic powder and 1g The binder (polyvinyl alcohol with a concentration of 4%) is mixed evenly; placed in a mold and maintained at a pressure of 30 MPa for 40 seconds, then demolded and taken out; sintered at 800°C for 60 minutes, and then the obtained core material 1 (compressed activated carbon filter layer 1) is sleeved in a circular ceramic layer body (ceramic powder molding layer 2) to synthesize the inner and outer layers.
[0071] Comparative Example 1
[0072] The difference from Example 1 is that the kaolin is replaced by alumina ceramic powder.
[0073] Comparative Example 2
[0074] The difference from Example 1 is that the filter element is a separate compressed activated carbon filter layer in Example 1 without adding microbead material 1.
[0075] Comparative Example 3
[0076] The difference from Example 1 is that the filter element is a separate molding layer of the ceramic powder in Example 1 without adding microbead material 2.
[0077] Table 1 Filter element performance test results of Examples 1-3 and Comparative Examples 1-3
[0078]
[0079] As shown in Table 1, the double-layer filter element of the present invention has the characteristics of large water flow rate and good filtration performance compared with the pure activated carbon filter element, and can effectively reduce the adsorption burden of activated carbon. Compared with the embodiment, in Comparative Example 1, the raw material is replaced with alumina ceramic powder, resulting in a decrease in removal rate; in Comparative Example 2, since the compressed activated carbon filter layer does not add microbead material 1, the filtration is insufficient, the water outlet rate is basically unchanged, but the removal rate is greatly reduced; in Comparative Example 3, since the ceramic powder molding layer does not add microbead material 2, the water outlet rate is slowed down, there are no nanopores, and the removal rate will also decrease.
[0080] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A water treatment filter element, characterized in that: A double-layer filter element structure comprising an inner layer and an outer layer; one of the inner layer and the outer layer comprises activated carbon material and microbead material 1 with open pores, and the other layer comprises ceramic powder with pore distribution from nanometer to micrometer level and microbead material 2 with open pores.
2. A method for preparing a water treatment filter element according to claim 1, characterized in that: The microbead material 1 and the activated carbon powder are mixed evenly and then pressed to obtain a core material 1; The micro-bead material 2, ceramic powder and binder are mixed evenly, molded, sintered, and then assembled with the core material to form an inner and outer layer to obtain the product.
3. The preparation method according to claim 2, characterized in that: The microbead material 1 and activated carbon powder are 20-40 parts and 60-80 parts by mass respectively.
4. The preparation method according to claim 2 or 3, characterized in that: The particle size of the activated carbon is 1-150 μm; And / or, the particle size of the microbead material 1 is 100-300 μm, and the bulk density is 0.75-0.85 g / cm 3 , porosity 30-40%.
5. The preparation method according to claim 2, characterized in that: The microbead material II, ceramic powder and binder are 40-60 parts, 90-110 parts and 0.1-5 parts by mass respectively.
6. The preparation method according to claim 2 or 5, characterized in that: The particle size of the microbead material 2 is 0-250 μm, and the bulk density is 0.40-0.50 g / cm 3 , porosity 75-85%, pore size range 5nm-1μm, specific surface area 180-195m 2 / g.
7. The preparation method according to claim 2, characterized in that: The molding is performed by maintaining the pressure at 5-30 MPa for 40-80 seconds and then demolding and taking out.
8. The preparation method according to claim 2, characterized in that: The sintering step is to sinter the formed product at 800-1000° C. for 60-120 min.
9. The preparation method according to claim 2, characterized in that: The ceramic powder raw material includes one or more of kaolin, purple clay or red clay.
10. The preparation method according to claim 2, characterized in that: The specific surface area of the ceramic powder is 10-300m 2 / g, particle size is 20-300μm.
Citation Information
Patent Citations
Purified water taste adjuster and production method thereof
CN109850982A
Preparation method and application of light porous ceramic hollow microspheres
CN111484351A
Ceramic-based porous sewage treatment agent and preparation method thereof
CN116332672A